FPGACam: A FPGA based efficient camera interfacing architecture for real time video processing - Sayantam Sarkar; Satish S. Bhairannawar; Raja K.B. (IET Circuits, Devices and Systems)
Abstract In most of the real time video processing applications, cameras are used to capture live video with embedded systems/Field Programmable Gate Arrays (FPGAs) to process and convert it into the suitable format supported by display devices. In such cases, the interface between the camera and display device plays a vital role with respect to the quality of the captured and displayed video, respectively. In this paper, we propose an efficient FPGA‐based low cost Complementary Metal Oxide Semiconductor (CMOS) camera interfacing architecture for live video streaming and processing applications. The novelty of our work is the design of optimised architectures for Controllers, Converters, and several interfacing blocks to extract and process the video frames in real time efficiently. The flexibility of parallelism has been exploited in the design for Image Capture and Video Graphics Array (VGA) Generator blocks. The Display Data Channel Conversion block required for VGA to High Definition Multimedia Interface Conversion has been modified to suit our objective by using optimised Finite State Machine and Transition Minimiszed Differential Signalling Encoder through the use of simple logic architectures, respectively. The hardware utilization of the entire architecture is compared with the existing one which shows that the proposed architecture requires nearly 44% less hardware resources than the existing one.